Microcrédito : uma política social de redução da pobreza? - Colodeti, Vicente de Paulo (2016)
Made available in DSpace on 2016-12-23T14:36:52Z (GMT). No. of bitstreams: 1 Vicente Colodeti.pdf: 1082003 bytes, checksum: 27b6df3da25d187fb53c689d312852e7 (MD5) Previous issue date: 2011-12-16